Colloidal network oleogels structured by sonothermal conjugates of sodium caseinate and anionic gums. (July 2023) - Tirgarian, Behraad; Farmani, Jamshid; Farahmandfar, Reza; Milani, Jafar M.; Van Bockstaele, Filip
Abstract: Food-grade colloidal network oleogels prepared by high internal phase emulsion (HIPE) templates are innovative systems in the field of solid fat mimetics. However, finding a colloidal stabilizer with outstanding interfacial activity that can stabilize the oleogels throughout storage (without oil-off) is still an uphill task. Herein, conjugates were prepared via sonothermal glycation of sodium caseinate (SC) with κappa -carrageenan (kC) or Alyssum homolocarpum seed gum (AHSG) and then successfully utilized in the stabilization of HIPEs. Emulsions were then oven-dried to obtain the oleogels. It was observed that HIPE stabilized by SC-AHSG conjugate prepared by 30 min sonication pretreatment (SC-AHSG30) resulted in the lowest mean droplet size (1.75 ± 0.01 μm) and polydispersity (0.47 ± 0.04) as well as the highest zeta potential (−33.43 ± 0.12 mV), centrifugal stability (82.20 ± 0.43%) and storage stability. This was justified by the highest glycation degree and interfacial activity of SC-AHSG30 conjugate. Likewise, the HIPE-templated oleogel stabilized by SC-AHSG30 conjugate revealed the highest apparent viscosity, gel strength (complex modulus = 621.80 ± 4.68 kPa), melting temperature (115.45 ± 0.65 °C), induction period of oxidation (25.14 ± 0.05 days) and was ultra-stable throughout 30-days of storage (no oil-off was noticed). This research confirms that sonothermally-glycated food hydrocolloids can be utilized as superb liquid oil structurants. Graphical abstract: Image 1 Highlights: Sonication (10–30 min) was used to promote the conjugation of SC-anionic gums. Sonication for 30 min led to the highest glycation degree and interfacial activity. AHSG was more reactive with SC than kC, providing a better HIPE stabilizing effect. Sonication and polysaccharide type affected the properties and stability of oleogels. HIPE-templated oleogels stabilized by Maillard conjugates were ultra-stable.